Samuel Davidson papers - Davidson, Samuel, -1810.
Business and personal correspondence, daybook, and ledger of accounts. Includes material relating to changes made in Pierre L'Enfant's manuscript plan of the President's Square (now Lafayette Park) which Davidson, who owned land nearby, claimed had marred the Federal City's beauty and lowered property values. Correspondents include city commissioners, L'Enfant, Thomas Jefferson, and George Washington.
Merchant of Georgetown, Washington, D.C.
Collection material in English.
Keywords: Jefferson, Thomas, -- 1743-1826 -- Correspondence; L'Enfant, Pierre Charles, -- 1754-1825.; L'Enfant, Pierre Charles, -- 1754-1825 -- Correspondence; Washington, George, -- 1732-1799 -- Correspondence; United States. -- Commissioners of the City of Washington; City planning -- Washington (D.C.); Real property -- Washington (D.C.); Lafayette Park (Washington, D.C.); Washington (D.C.) -- Commerce; Washington (D.C.) -- Description and travel; Merchants